Difficulties of undergraduate students in the organic chemistry laboratory - Lorenzo, Maria Gabriela (2012)
In order to study the learning difficulties of university students in the organic chemistry laboratory, a new Model for the Analysis of Experimental Work (MAEW) was developed. This article is organized into three parts: first, a historical look at the role of experimental work in science education, including the purpose of the laboratory class; next, a description of the MAEW; finally, we show how the MAEW can be applied to an actual laboratory class of organic chemistry. An original proposal for the classification of the materials used in an organic chemistry laboratory is also offered.